COVID -19. THE PANDEMIC IN VENEZUELA - Gotera, Jennifer (2021)
In China in the beginning of December 2019, the first cases of pneumonia of unknown etiology were identified in the city of Wuhan. Subsequently, it was discovered that the cause of this infection was a type of coronavirus, called SARS-CoV-2, and COVID-19 the disease that it produces. Currently, the American continent is the most affected, and Venezuela does not escape the world reality. After the confirmation of the first cases in the country, the Ministry of Popular Power for Health [MPPS], through the database of the Unified Health Information System [SUIS], expressed stability in the incidence of cases until the middle of May 2020, when the curve of confirmed cases presented an abrupt change, this mostly related to imported cases from neighboring countries. The virus mainly affects people under 40, with a significant proportion of asymptomatic cases and a low mortality rate in Venezuela. However, despite all the efforts made and the health measures implemented, the number of infections and the rapid spread of the virus continue to rise. This research will analyze the situation of COVID-19 in the Bolivarian Republic of Venezuela, which will allow us to know how this new disease is affecting the population of the country